Sex allocation and field population sex ratio of Apanteles taragamae Viereck (Hymenoptera: Braconidae), a larval parasitoid of the cucumber moth Diaphania indica Saunders (Lepidoptera: Crambidae) - Nurkomar Ihsan (De Gruyter, 2021)
Sex ratio is one of the most important biological characteristics of arthropods. In a parasitoid population, sex ratio can influence the suppression of host populations or the stability of host–parasitoid interactions in the field. In this study, a survey was carried out to determine the sex allocation through the sequence of male/female adult emergence and calculate the sex ratio of selected populations of Apanteles taragamae in their natural habitat. Assessment of sex ratio at the population and individual level (brood size per female) was examined. We found no difference in the likelihood that either sex would emerge before the other. Observations of sex ratio at the population and individual level reveal a females biased sex ratio. Analysis of the relationship between brood size and sex ratio of A. taragamae shows that brood size may influence the proportion of male to female offspring yielded. A male-biased sex ratio tends to be found in smaller brood size. However, sex ratio is shifted to female biased in larger brood size.